AI Structuralist Storytelling In Computer Games - Fairclough, Chris; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 2004)
This paper is a description of our work in creating a story director agent which utilises AI techniques. The story director controls the storyline in an adventure computer game, with the player controlling the hero character, and the story director reacting to the player's actions. The story is told through subplot-level plans being formulated with a case-based planner, and a social simulation system that the story director is 'plugged in to', allowing consistent logical stories while allowing for player freedom. The system has been named OPIATE ? Open-ended Proppian Interactive Adaptive Tale Engine.
Keywords: Interactive story; case-based planning; computer games